Management of Paediatric Cardiac Arrest due to Shockable Rhythm-A Simulation-Based Study at Children's Hospitals in a German Federal State - Nadine Mand; Marieke Hoffmann; Anja Schwalb; Andreas Leonhardt; Martin Sassen; Tina Stibane; Rolf Felix Maier; Carolin Donath (MDPI AG, 2024)
(1) Background: To improve the quality of emergency care for children, the Hessian Ministry for Social Affairs and Integration offered paediatric simulation-based training (SBT) for all children's hospitals in Hesse. We investigated the quality of paediatric life support (PLS) in simulated paediatric resuscitations before and after SBT. (2) Methods: In 2017, a standardised, high-fidelity, two-day in-house SBT was conducted in 11 children's hospitals. Before and after SBT, interprofessional teams participated in two study scenarios (PRE and POST) that followed the same clinical course of apnoea and cardiac arrest with a shockable rhythm. The quality of PLS was assessed using a performance evaluation checklist. (3) Results: 179 nurses and physicians participated, forming 47 PRE and 46 POST interprofessional teams. Ventilation was always initiated. Before SBT, chest compressions (CC) were initiated by 87%, and defibrillation by 60% of teams. After SBT, all teams initiated CC (p = 0.012), and 80% defibrillated the patient (p = 0.028). The time to initiate CC decreased significantly (PRE 123 ± 11 s, POST 76 ± 85 s, p = 0.030). (4) Conclusions: The quality of PLS in simulated paediatric cardiac arrests with shockable rhythm was poor in Hessian children's hospitals and improved significantly after SBT. To improve children's outcomes, SBT should be mandatory for paediatric staff and concentrate on the management of shockable rhythms.